2021
DOI: 10.1371/journal.pone.0251311
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological blood pressure control and outcomes in patients with hypertensive crisis discharged from the emergency department

Abstract: Pharmacological blood pressure (BP) intervention for high blood pressure is controversial for a wide spectrum of hypertensive crisis in the emergency department (ED). We evaluated whether medical control of BP altered the short- and long-term outcomes among patients with hypertensive crisis who were discharged from the ED under universal health care. This retrospective cohort comprised 22 906 adults discharged from the ED of a tertiary hospital with initial systolic BP ≥ 180 mmHg or diastolic BP ≥ 120 mmHg bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
2
2
0
Order By: Relevance
“…To our knowledge, our study is currently the only one that prospectively and systematically assesses short-term (72 hours) BP control in office setting after ED discharge, except for a small study on 21 hypertensive patients in which 24h-ABPM immediately after discharge from the ED [ 47 ]. Approximately 90% of patients in our study were discharged from the ED with BP < 180/110 mmHg, thus no longer meeting the criteria for HU, for those without organ damage; a similar rate has been described in recent studies [ 48 , 49 ]. In about one-third of the cases, normal office BP was present at 72 hours after ED discharge; similar outcome than that reported, of about 20% at 2 weeks after discharge, in a retrospective study conducted in the Thai population [ 49 ], but very different from the previously cited Israeli report in which 17 out of 21 patients remained with a SBP > 180 mmHg 24 hours after ED discharge [ 47 ].…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, our study is currently the only one that prospectively and systematically assesses short-term (72 hours) BP control in office setting after ED discharge, except for a small study on 21 hypertensive patients in which 24h-ABPM immediately after discharge from the ED [ 47 ]. Approximately 90% of patients in our study were discharged from the ED with BP < 180/110 mmHg, thus no longer meeting the criteria for HU, for those without organ damage; a similar rate has been described in recent studies [ 48 , 49 ]. In about one-third of the cases, normal office BP was present at 72 hours after ED discharge; similar outcome than that reported, of about 20% at 2 weeks after discharge, in a retrospective study conducted in the Thai population [ 49 ], but very different from the previously cited Israeli report in which 17 out of 21 patients remained with a SBP > 180 mmHg 24 hours after ED discharge [ 47 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our sample also had a significant proportion of patients with dyslipidemia (39.5%), which aligns with expectations given local dietary habits though it contrasts with findings from other studies conducted in Italy [5]. Blood pressure values at admission were similar in our study compared to other reports [5,8].…”
Section: Discussionsupporting
confidence: 81%
“…While we found a slight predominance of women (50.6%), some studies reported significantly higher percentages of men [7]. Additionally, the number of patients with a history of diabetes varied across different studies (6,7,8), possibly due to differences in therapy, lifestyle habits, ethnicity, and sample selection. The prevalence of smokers in our sample (29.6%) fell between the percentages reported in other studies, which could reflect differences in anti-smoking campaigns and patient reporting accuracy.…”
Section: Discussionmentioning
confidence: 50%
“…Major organ systems included the central nervous, cardiovascular, renal, and gravid uterus. Activation of the renin-angiotensin aldosterone system seems to be significant in the pathophysiology of severe hypertension [11][12][13][14][15][16][17].…”
Section: Pathophysiologymentioning
confidence: 99%